Mehrsprachigkeit beim Erwerb der Zweitfremdsprache (Deutsch nach Englisch) in den allgemeinbildenden Bildungseinrichtungen der Ukraine. Mehrsprachigkeit, Interkulturelle Kommunikation, Sprachvermittlung: Internationale Perspektiven auf DaF und Herkunftssprachen - Labinska, Bohdana; Chearska, Zhanna (Berlin, Bern, Bruxelles, New York, Oxford, Warszawa, Wien: Peter Lang Verlag., 2021)
The learning of German as the second foreign language based on the learning of English (the first foreign language) at the secondary schools of Ukraine has been analyzed. With regard to the current didactic researches, the influence of the native language (Ukrainian) and the first foreign language (English) on the learning of the second foreign language (German) has been studied in the article. The historical conditions of the Ukrainian language development (the influence of German on the development of Ukrainian in the epoch of the Habsburg monarchy) facilitate the student’ understanding of the new modern German vocabulary at the German lessons.
Keywords: foreign language, German lessons, second foreign language